1996
DOI: 10.1104/pp.112.1.249
|View full text |Cite
|
Sign up to set email alerts
|

NAD(P)H:(Quinone-Acceptor) Oxidoreductase of Tobacco Leaves Is a Flavin Mononucleotide-Containing Flavoenzyme

Abstract: The soluble NAD(P)H:(quinone-acceptor) oxidoreductase [NAD(P)H-QR, EC 1.6.99.21 of Nicotiana fabacum L. leaves and roots has been purified. NAD(P)H-QR contains noncovalently bound flavin mononucleotide. Pairs of subunits of 21.4 kD are linked together by disulfide bridges, but the active enzyme is a homotetramer of 94 to 100 kD showing an isoelectric point of 5.1. NAD(P)H-QR is a B-stereospecific dehydrogenase. NADH and NADPH are electron donors of similar efficiency with K,,,:K, ratios (with duroquinone) of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 29 publications
7
39
0
Order By: Relevance
“…1B), these data are in agreement with the finding that plant NQRs are homotetramers of 21.5-kD subunits (Sparla et al, 1996(Sparla et al, , 1999. Beyond that, the enzyme demonstrates an immunological relationship to AtNQR identified by Sparla et al (1999) rather than to AtFQR1 identified by Laskowski et al (2002).…”
Section: á2supporting
confidence: 81%
See 1 more Smart Citation
“…1B), these data are in agreement with the finding that plant NQRs are homotetramers of 21.5-kD subunits (Sparla et al, 1996(Sparla et al, , 1999. Beyond that, the enzyme demonstrates an immunological relationship to AtNQR identified by Sparla et al (1999) rather than to AtFQR1 identified by Laskowski et al (2002).…”
Section: á2supporting
confidence: 81%
“…Examples of this class are the NAD(P)H:quinone-acceptor oxidoreductases known as DT-diaphorases in animals (Lind et al, 1990;Ross, 1997). Functionally related flavoenzymes have also been found in plants (Spitsberg and Coscia, 1982;Luster and Buckhout, 1989;Valenti et al, 1990;Serrano et al, 1994;Rescigno et al, 1995;Trost et al, 1995Trost et al, , 1997Sparla et al, 1996Sparla et al, , 1998 (Iyanagi and Yamazaki, 1970;Lind et al, 1990;Sparla et al, 1996;Ross, 1997). A purified quinone oxidoreductase investigated by Trost et al (1997) was shown to be insensitive to DPI.…”
Section: Effects Of Oxidoreductase Inhibitorsmentioning
confidence: 99%
“…Transcripts for both QR1 and QR2 are rapidly upregulated in Triphysaria roots as a primary response to treatment with DMBQ and other quinones (Matvienko et al, 2001b). Based on sequence homologies, QR1 was classified as a member of the z-crystallin-like quinone oxidoreductases (EC 1.6.5.5) (Thorn et al, 1995;Edwards et al, 1996) and QR2 as a quininereducing flavoprotein (EC 1.6.5.2) (Sparla et al, 1996;Matvienko et al, 2001b). Later purifications of the QR2 enzyme showed that it catalyzes NAD(P)H-dependent quinone reduction with substrate and inhibitor specificity consistent with its placement into the Diaphorase family (Sparla et al, 1999;Wrobel et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Since the activity of the soluble form was hardly sensitive to DPI, it seems possible that the DPI-binding site and the actual QR site are not on the same polypeptide. Since the soluble enzyme contains FMN (Sparla et al 1996), the PM-bound QR can also be considered to be a flavoprotein. However, also in this case the PM preparation was not stripped properly.…”
Section: Quinone Reductasesmentioning
confidence: 99%
“…The QR activities from PM vesicles of zucchini hypocotyls were studied by Trost et al (1997) in order to reveal differences and similarities between the PM-bound and the soluble forms of NAD(P)H-(quinone-acceptor) oxidoreductases. A 24 kDa soluble form had previously been purified and characterized from sugar beet cells (Trost et al 1995) and tobacco leaves (Sparla, Tedeschi & Trost 1996) as soluble QR. In the case of zucchini, the PM-bound form showed three bands at 27, 24, and 18 kDa whereas the soluble form showed one band at 24 kDa.…”
Section: Quinone Reductasesmentioning
confidence: 99%